Answer:
Billie's age = x = 17 years
Tony's age = y = 31 years
Step-by-step explanation:
Let
Billie's age = x
Tony's age = y
Twice Billie’s age decreased by 3 is Tony’s age.
y = 2x - 3..... Equation 1
Tony is fourteen years older than Billie.
x = y - 14
We substitute y - 14 for x in Equation 1
y = 2x - 3..... Equation 1
y = 2(y - 14) - 3
y = 2y - 28 - 3
y - 2y = -28 - 3
-y = -31
y = 31 years
Solving for x
x = y - 14
x = 31 - 14
x = 17 years.
Therefore:
Billie's age = x = 17 years
Tony's age = y = 31 years
Answer: A and B
Explanation: I’ll use A as an example. When you multiply the bottom equation by -3/2, the equation becomes: -9x+6y=-3. Then, proceed to add the equations. Look at X and Y in both equations: do the Y variables in both equations equal to 0 when added together? Yes, because -6y+6y=0! Therefore, you can eliminate y in these two equations.
Hope that’s helps シ
The
<u>correct answer</u> is:
Explanation:
The symmetric property states that if two quantities are equal (or congruent), you can "flip" them around the equals sign (or congruence sign).
This means since EFG is congruent to HJK, then HJK is congruent to EFG.
Answer:
<h2>it's simple<u>i</u><u>j</u><u>e</u><u>j</u><u>o</u><u>o</u><u>e</u><u>j</u><u>e</u><u>j</u><u>j</u><u>e</u><u>j</u><u>e</u><u>k</u><u>e</u></h2>